Biografías de los miembros del Comité Nacional: Francisco Azorin, Molina Conejero, Ignacio Ferretjans, Rafael Henche de la Plata, Antonio LLaneza, Ernesto Mareen López, Ramón Solar Pilatti y Narciso Vázquez Torres (1938). - Archivo y Biblioteca de la Fundación Pablo Iglesias; PARTIDO SOCIALISTA OBRERO ESPAÑOL, 1879-1939 (Archivo y Biblioteca de la Fundación Pablo Iglesias)
Sin determinar